Mobilizing for accountability contentious politics in the anti-Estrada campaign - Arugay, Aries A. (2004)
The anti-Estrada campaign that culminated in the so-called People Power II la
January 2001 can be viewed as a testament to the efficacy and strength of collect
mobilization in the Philippines. This paper discusses the mobilization in the fo
of protests and other mass actions as a strategy of civil society aimed at eliciting
accountability from President Estrada. Utilizing the theory of contentious politics
and the different strategies of the societal accountability framework, it examines t
mobilization conducted by some civil society organizations (CSOs) from October 20
to January 2001. It argues that the interplay of available mobilizing structures such
the Kongreso ng Mamayang Pilipino (Kompil II) and the Estrada Resign Movem
(ERM), the collective action frames that focused on failure, impunity and injustice, t
traditional and innovational forms of contention, and the existence of crucial politi
opportunities made the protest actions in the anti-Estrada campaign possible.
concludes by arguing that the shape and dynamics of future political mobilization
by civil society would be greatly influenced by this contentious po